2020
DOI: 10.1111/ijcp.13892
|View full text |Cite
|
Sign up to set email alerts
|

Is mean platelet volume a predictive marker for the diagnosis of COVID‐19 in children?

Abstract: Aim To investigate the mean platelet volume (MPV) in asymptomatic children infected with COVID‐19. Methods The study included 55 children infected with COVID‐19 and 60 healthy children for the comparison of leukocyte and thrombocyte count, MPV and serum C‐reactive protein (CRP) levels. Demographic data and clinical findings of all the participants were recorded, including age, gender, weight, temperature, cough, shortness of breath and contact history. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 29 publications
1
14
1
1
Order By: Relevance
“…In the present study, the MPV level of positive paediatric cases was found to be statistically significantly higher than negative cases. In the study of Gümüs et al, MPV level was found to be significantly higher in paediatric positive cases, and they predicted that this was a predictive value to help diagnosis, especially in asymptomatic paediatric cases [21]. The findings of the present study also support this result.…”
Section: Discussionsupporting
confidence: 85%
“…In the present study, the MPV level of positive paediatric cases was found to be statistically significantly higher than negative cases. In the study of Gümüs et al, MPV level was found to be significantly higher in paediatric positive cases, and they predicted that this was a predictive value to help diagnosis, especially in asymptomatic paediatric cases [21]. The findings of the present study also support this result.…”
Section: Discussionsupporting
confidence: 85%
“…Several studies have reported that MPV changes are associated with morbidity and mortality in patients with diseases such as sepsis, diabetes mellitus, myocardial infarction, and chronic inflammatory disorders [8][9][10][11] . Although there are several studies about the association of MPV with the diagnosis, morbidity, and mortality of COVID-19 patients, the results were contradictory [11][12][13][14] . Since we thought that these conflicting results seen in previous studies were due to their small number of patient groups or their study design, we aimed to investigate the effects of MPV on hospitalization and mortality with a large patient population.…”
mentioning
confidence: 99%
“…Platelets, in addition to being the major cells in thrombosis and homeostasis, are also involved in inflammatory processes and immune responses [153] , [154] , [155] , [156] , [157] . Adverse changes in the platelet count and function are responsible for coagulation drawbacks and thrombotic complications in COVID-19 patients and increase the risk of lethal outcomes [156] , [158] , [159] , [160] , [161] , [162] .…”
Section: Plateletsmentioning
confidence: 99%
“…An increase in the mean platelet volume (MPV) is directly related to the severity of COVID-19 disease and the rate of platelet activation [155] , [162] , [166] , [168] . However, a prospective study of asymptomatic children that tested positive for SARS-CoV-2 infection found a high MPV even without any clinical signs ( Table 4 ) [154] . A possible underlying mechanism for a high MPV in COVID-19 patients may be an increase in the release of young platelet in response to platelet destruction after infection and cytokines such as IL-6 [154] , [157] .…”
Section: Plateletsmentioning
confidence: 99%
See 1 more Smart Citation